Research on the Psychological Expectation Impact on Enterprise Innovation Under Mergers and Acquisitions Pressure: From the Evidence of Large Stock Dividends - Kuang, XueWen; Li, ZeYu; Lin, He (Frontiers in Psychology, 2021)
From the perspective of social psychology, takes the large stock dividends policy of Chinese listed companies as an example, based on the sample of Chinese listed companies from 2009 to 2018, this article examines the impact of psychological expectation under the mergers and acquisitions (M&A) pressure on enterprise innovation. The empirical study finds that the high dividend payout mainly increases the liquidity of the stock, which makes the company face a greater risk of hostile merger and acquisition, and thus causes the management to pay attention to the psychological preference of short-term effect, and reduces the level of enterprise R&D and innovation. Moreover, the above conclusion is still true after controlling the endogenetic problem. Further research shows that in private enterprises, enterprises with low ownership concentration and non-high-tech enterprises, large stock dividends has a more obvious inhibiting effect on the level of enterprises’ R&D and innovation. After excluding the possible of agency problem, the conclusion is still robust. This article expands the research on the influencing factors of enterprise innovation from the perspective of psychological expectation. The findings of this study provide references and inspirations for facilitating enterprise innovations by reducing short-sighted behaviors of management under increased stock liquidity.